KEPRAKTISAN MODEL E-STEM PJBL DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Syarifah Rahmiza Muzana; Silvi Puspa Widya Lubis; Hasanah Hasanah; Wirda Wirda; Rahmati Rahmati; Nurlaila Nurlaila (Jurnal Dedikasi Pendidikan, 2023)
This study aims to determine the practicality of the PjBL E-STEM model in science learning to improve problem solving abilities faced by students at the junior high school level. The practicality level of the PjBL E-STEM model in science learning is measured through the results of observer tests that are included in the learning process in class. The criterion for the acceptance of the practicality level of the model developed according to the expert is that at least the practical level obtained is in the "quite practical" category. The data collection technique used the PjBL E-STEM model implementation questionnaire in science learning. Qualitative data analysis used content analysis techniques while quantitative data were analyzed using descriptive statistics. The results showed that the practicality of the PJBL E-STEM model in science learning resulted in an average score of 88.25 in the practical category